The Influence of Service Quality on Outpatient Loyalty in the Specialist Polyclinic - Monika Saraswati Sitepu; Rizka Usi Nadhifa; Detty Isniaty; Siti Maemun (Indonesian Journal of Global Health Research, 2026)
Service quality is considered an important factor in building patient loyalty. The aim of this study is to assess hospital service quality from the patients’ perspective and to determine the importance of each quality dimension in predicting patient loyalty. To evaluate the structural construct of hospital service quality from the patients’ perspective and to determine the importance of quality dimensions in predicting patient loyalty. This was an analytical study with a cross-sectional design conducted in 2025. The study population consisted of outpatient individuals aged ≥18 years who had visited at least twice, with a total sample of 164 respondents. The research variables included demographics, service quality, and patient loyalty. The study instrument used a validated and reliable questionnaire; the service quality variable comprised 5 dimensions with 27 statements, while the loyalty variable consisted of 9 indicators with 27 statements. Multivariate analysis was performed using multiple logistic regression with a significance level of α = 5%. Both loyal and non-loyal patients were predominantly female, of productive age, lived ≥5 km from the hospital, had an education level of elementary to senior high school, were non-workers, and used insurance as their payment source. There was a significant relationship between all five dimensions of service quality (tangibles, reliability, responsiveness, assurance, and empathy) and patient loyalty (p < 0.001). Tangible was the most dominant factor influencing patient loyalty (adjOR = 5.68; 95% CI: 1.96–16.41), followed by responsiveness (adjOR = 4.63; 95% CI: 1.51–14.15) and assurance (adjOR = 5.54; 95% CI: 1.90–16.19), which also had a significant effect on patient loyalty. Patients’ experiences with hospital services have a significant impact on outcome variables such as their willingness to return to the same hospital, reuse its services, or recommend it to others. The relationship between service quality and patient loyalty demonstrates its strategic importance in improving service quality to attract and retain patients as well as to expand market share.